Imaging characteristics and neurosurgical outcome in subjects with agenesis of the corpus callosum and interhemispheric cysts. - Severino, Mariasavina; Tortora, Domenico; Reid, Catriona; Uccella, Sara; Nobili, Lino; Accogli, Andrea; Srour, Myriam; Ramaglia, Antonia; Sudhakar, Sniya; Consales, Alessandro; Pavanello, Marco; Piatelli, Gianluca; et al. (Neuroradiology, 2022)
Purpose: To explore the relationships between clinical-radiological features and surgical outcomes in subjects with interhemispheric cysts (IHC) and corpus callosum anomalies. Methods: We reviewed the clinico-radiological and neurosurgical data of 38 patients surgically treated with endoscopic fenestration, shunting, or combined approaches from 2000 to 2018 (24 males, median age 9 years). Pre- and postoperative changes in IHC volume were calculated. Outcome assessment was based on clinico-radiological data. Group comparisons were performed using χ2, Fisher exact, Mann–Whitney U, and Kruskal–Wallis tests. Results: Median age at first surgery was 4 months (mean follow-up 8.3 years). Eighteen individuals (47.3%) required > 1 intervention due to IHC regrowth and/or shunt malfunction. Larger preoperative IHC volume (P =.008) and younger age at surgery (P =.016) were associated with cyst regrowth. At last follow-up, mean cystic volume was 307.8 cm3, with IHC volume reduction > 66% in 19/38 (50%) subjects. The neurological outcome was good in 14/38 subjects (36.8%), fair in 18/38 (47.3%), and poor in 6/38 (15.7%). There were no differences in the postoperative cyst volume with respect to either the type of first surgery or overall surgery type. Higher absolute postoperative IHC reduction was observed in subjects who underwent both IHC fenestration and shunting procedures (P <.0001). No differences in neurological outcome were found according to patient age at surgery or degree of IHC reduction. Conclusion: Endoscopic fenestration and shunting approaches are both effective but often require multiple procedures especially in younger patients. Larger IHC are more frequently complicated by cyst regrowth after surgery.